1994
DOI: 10.1017/s0266467400008063
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of gaps along three catenas in the moist forest of Taï National Park, Ivory Coast

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Cambridge University Press is collaborating with JSTOR to digitize, preserve and extend access to Journal of Tropical Ecology.http://www.jstor.org ABSTRACT. The spatial distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 19 publications
(20 reference statements)
1
54
1
4
Order By: Relevance
“…Greater gap area fractions at higher slopes have been found for other sites. Poorter et al (1994) found higher gap area fractions on the upper and middle slope than on the crest or lower slope.…”
Section: Determinants Of Variation In the Gap Area Fractionmentioning
confidence: 73%
See 2 more Smart Citations
“…Greater gap area fractions at higher slopes have been found for other sites. Poorter et al (1994) found higher gap area fractions on the upper and middle slope than on the crest or lower slope.…”
Section: Determinants Of Variation In the Gap Area Fractionmentioning
confidence: 73%
“…In addition to problems arising from diverse criteria used to classify gaps, comparative studies also conflate effects of the external drivers to forest disturbance, e.g., storm frequency (Espirito-Santo et al, 2010) and rainfall regime (Foster and Brokaw, 1982), with intrinsic environmental factors that may also influence the probability of treefall e.g., soil type (Vandermeer et al, 1994;VanderMeer and Bongers, 1996;Ashton and Hall, 1992), topographic position (Poorter et al, 1994), and forest age (Numata et al, 2006). In this study, we provide the first analysis at the landscape scale of how forest age, topography and soil type influence gap disturbance patterns in a tropical forest.…”
Section: E Lobo and J W Dalling: Canopy Gap Disturbance In Tropicamentioning
confidence: 99%
See 1 more Smart Citation
“…However, spatial analysis conducted in the moist forest of Tal National Park in South-West Ivory Coast, West Africa, showed that the occurrence of gaps is often not random, with some sites more likely to have gaps than others places (Poorter et al, 1994). Other studies also suggested that canopy gaps in old-growth Neotropical lowland forests are not spatially randomly distributed, but rather clustered around specific sites such as those with shallow soils (Van der Meer & Bongers, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A high level of disturbance will result in many gaps or in large gaps. This will lead to a relatively high proportion of species depending on forests gaps (Poorter, Jans, Bongers, & Van Rompaey, 1994). Gap size may be computed by different methods based on two and three dimensional projections of the canopy gap.…”
mentioning
confidence: 99%